2010
DOI: 10.1001/archsurg.2010.228
|View full text |Cite
|
Sign up to set email alerts
|

Variability in Pediatric Splenic Injury Care

Abstract: General surgeons reported varying degrees of familiarity with and use of clinical practice guidelines for pediatric splenic injury management. Limited pediatric experience and lack of pediatric hospital resources may limit more widespread adoption of nonoperative management. Targeted educational interventions may help increase surgeon knowledge of guidelines and best practices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…4,18 Previous investigations have found benefit to instituting practice guidelines for splenic injury, 4,19,20 but have also shown that these guidelines are not widely known or used. 21 …”
Section: Discussionmentioning
confidence: 99%
“…4,18 Previous investigations have found benefit to instituting practice guidelines for splenic injury, 4,19,20 but have also shown that these guidelines are not widely known or used. 21 …”
Section: Discussionmentioning
confidence: 99%
“…Literature reports describe varying degrees of familiarity with and use of clinical practice guidelines for pediatric splenic injury management in the general surgeon group. Limited pediatric experience and a lack of pediatric hospital resources may limit the potential for a more widespread adoption of non-operative management approaches [10] . Especially in multi-trauma patients hemodynamic (in-) stability is not the only criterion for laparotomy.…”
Section: Discussion ▼mentioning
confidence: 99%
“…In the present series 32 % of laparotomies were performed for other indications than " hemodynamic instability " . But the term " hemodynamic instability " is also rather subjective [10] . The main challenge in the current management of the hemodynamically instable multi-trauma patient with intra-abdominal injury is defi ning the cause for the hemodynamic instability.…”
Section: Discussion ▼mentioning
confidence: 99%
“…57,13,14,16 Despite the high grades of organ injury and substantial overall injury in the HMC solid organ injury population, the overall splenectomy frequency of 4.0% among all pediatric splenic injury patients at HMC from 2005 to 2012 falls below published benchmarks of 5% to 11% in a nonisolated injury population. 1,19 This suggests that there may be opportunity for further reducing splenectomy frequency, particularly among severely injured patients.…”
Section: Discussionmentioning
confidence: 99%
“…Review of this experience has led to the publication of benchmarks of a splenectomy frequency of no more than 3% in children with isolated splenic injuries and of 5% to 11% in all children with splenic injury. 1 This goal seems to be achievable in a variety of care settings 24 without subjecting patients to increased risk of transfusion, urgent surgery, late complications, or mortality. 412 In nonoperatively managed patients, subsequent efforts aimed to decrease resource use showed that most may be successfully managed with relatively short intensive care unit (ICU) stays, relatively short hospital stays, limited laboratory draws, and limited repeat imaging tests.…”
mentioning
confidence: 99%